Evaluation of the Effectiveness of Internal Control Systems in Reducing Accounting Fraud in Financial Sector Companies - Waromi, Juliana; Kambuaya, Maylen K. P.; Wonar, Klara (Eastasouth Institute, 2024)
This research aims to evaluate the effectiveness of internal control systems (ICS) in reducing accounting fraud in the financial sector companies. The literature review method is used to analyze various sources of information related to the research topic. Findings indicate that ICS plays a crucial role in safeguarding the integrity and reliability of financial information of companies. Factors such as management commitment, organizational culture, implementation consistency, and external factors influence the effectiveness of ICS. We recommend companies to enhance management commitment to ICS, strengthen a culture that prioritizes integrity, maintain consistency in ICS implementation, and take proactive steps in addressing challenges and leveraging opportunities.